Pelaksanaan Konseling Pada Klien Pasca Pemasangan Intra Uterine Device (IUD) Oleh Bidan Di Bidan Praktik Mandiri (BPM) - Pintam Ayu Yastirin; Rosmala Kurnia Dewi; Yuni Sugiartini (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2015)
Background: One of the most important elements in achieving reproductive health services is access to quality offamily planning services. Enhancement of access to the quality of family planning services can be performed byproviding counseling in family planning services. Coverage of IUD users in Grobogan is still slightly (4.2%), so itis necessary to make and to do a distribution pattern of contraceptive use, and one of them is by counseling. Midwives have provided counseling to clients after IUD insertion, but the implementation is not accord to an existingstandards.Purpose: The purpose of research is to determine the determinant factors that influence post-insertion IUD (IntraUterine Device) counseling practice by the Independent Midwife Practice in Grobogan.Method: This type of research is analytic survey with cross sectional approach. The subjects of research are independent midwife practices (BPM) in Grobogan, with 60 of BPM samples. Data analysis was by univariate andbivariate phi coefficient test.Result: The study shows that counseling to clients after IUD insertion by independent midwife practices is influenced by the level of knowledge of midwives. Statistically shows that there is relationship between the midwifeknowledge about IUD counseling to the implementation of counseling. It can be seen from p value 0,014<0,05.Conclusion: Based on the result of this study concluded that the counseling services by the midwife and wasstrongly influenced by the level of knowledge. Midwife who has a wealth of information about the IUD would beeasier to pass information to their clients.Keywords: Counseling, IUD contraception